2022
DOI: 10.4236/ojog.2022.1210089
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Amniotic Fluid Index versus Single Deepest Vertical Pocket Measurement at Term as a Predictor of Adverse Perinatal Outcome

Abstract: Introduction: Oligohydramnios is an important sign of fetal jeopardy and amniotic fluid index (AFI) and single deepest vertical pocket (SDVP) have been used to detect it. Objective: To compare AFI vs. SDVP at term as a predictor of adverse perinatal outcomes. Methods: A prospective observational study was conducted in Teaching Hospital Kandy, Sri Lanka for eight months from July 2015 to March 2016. 448 Singleton pregnancies admitted after 37 completed weeks were included. AFI ≤ 5 cm and SDVP < 2 cm were the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Oligohydramnios can be caused by multiple fetal factors, including placental malfunction, chromosomal abnormalities, medication adverse effects, and premature membrane rupture. Consequences include a higher rate of cesarean sections, meconium aspiration syndrome, critical care unit admission, and low APGAR score in newborns [ 2 ]. The results of the routine antenatal imaging with ultrasound (RADIUS) experiment, which was done on patients with isolated oligohydramnios (IO), showed that fetal growth was unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…Oligohydramnios can be caused by multiple fetal factors, including placental malfunction, chromosomal abnormalities, medication adverse effects, and premature membrane rupture. Consequences include a higher rate of cesarean sections, meconium aspiration syndrome, critical care unit admission, and low APGAR score in newborns [ 2 ]. The results of the routine antenatal imaging with ultrasound (RADIUS) experiment, which was done on patients with isolated oligohydramnios (IO), showed that fetal growth was unaffected.…”
Section: Introductionmentioning
confidence: 99%